Assistance in digital marketing and MSME accounting to support the business sustainability of Talatik home industry - Purwantini, Anissa Hakim; Khasanah, Lukluul; Pravitasari, Rahma; Syivani, Puspa Aini; Lestari, Ika; Azis, Rahajeng Reyhastuti (Community Empowerment, 2025)
The Talatik home industry has been around for about two years and has experienced several obstacles to maintain business sustainability. This community service activity aims to increase the knowledge and skills of Talatik MSME human resources related to digital marketing and financial bookkeeping. The methods used are training and mentoring the implementation of digital marketing and MSME accounting. The results of the activity showed that Talatik MSMEs already have an Instagram account used for online promotion which has an impact on increasing sales by 15%. This is also supported by a new logo and packaging that strengthens product branding. In addition, Talatik SMEs have also been able to carry out simple bookkeeping so that they can determine business profits and future business strategies that lead to business sustainability.